Pengaruh Beban Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan - Nadila Andra Kurnia; David Humala Sitorus (Value : Jurnal Manajemen dan Akuntansi, 2022)
The achievement of goals in an organization is strongly influenced by employee performance. Every organization will try to work on the presentation of its employees so that organizational goals can be achieved. One of the variables that can affect individual presentations is workload and work discipline. Implementation evaluation is expected to find out the results or level of achievement of a worker. The purpose of this study is to determine the extent to which workload and work discipline significantly affect the shipping company at Sicepat Express Batam. In this study, the population of this study were all employees of Sicepat Express Batam, which collected 115 people and the sample taken was the number of delivery parts for Sicepat Express Batam, which amounted to 115 people, using the multiple linear regression analysis method, namely Y = 4.091+ 0.118 X1 + 0.803 X2. The results of the T test partially prove, the results of the study state that workload and work discipline have a significant effect on employee performance at Sicepat Express Batam employees and the coefficient of determination (R2) obtained is 58.2% employee performance is influenced by workload and work discipline variables, and 41.8% influenced by other variables. Keywords: Workload, Work Discipline, Employee Performance.